Some ordered hypersemigroups which enter their properties into their σ-classes - Niovi Kehayopulu (Journal of Hyperstructures)
An important problem in the theory of ordered hypersemigroups is to describe the ordered hypersemigroups which enter their properties into their σ-classes. In this respect, we prove the following: If H is a regular, left (right) regular, completely regular, intra-regular, left (right) quasi-regular, semisimple, k regular, archimedean, weakly commutative, left (right) simple, simple, left (right) strongly simple ordered semigroup and σ a complete semilattice congruence on H then, for each a ∈ H, the σ-class (a)σ of H is, respectively, so.